EVALUATION OF THE INTERNAL CONTROL SYSTEM FOR INVENTORY AT U.D NINA USMAN SPBU - Sigit Sukmono; Jalinas Jalinas (Asosiasi Dosen Muda Indonesia, 2023)
A trading company can be defined as an organization that carries out business activities by purchasing goods from other companies and then selling them back to the public. Inventory is merchandise that is purchased and then stored for sale in the company's normal operations so that the company can pay more attention to inventory. Inventory is highly susceptible to damage and theft. Internal control also aims to protect company assets and also ensure that information regarding company inventory can be trusted. With internal control analysis, it is hoped that companies will be able to determine inventory more effectively and adequately. With effective internal control, it is hoped that they can minimize the risk of errors and fraud in merchandise inventory and if errors and fraud occur they can be immediately identified and resolved. The aim of this research is to determine the implementation of the internal control system at UD Nina Usman, which plays a role in supporting the company's internal control of inventory, and to find out how well the company carries out internal inventory control. The data used is primary data. The method used was observation and interviews to obtain information from the U.D Nina Usman gas station. The results of this research indicate that the inventory system at the U.D Nina Usman gas station is in accordance with an adequate internal control system using the COSO (Committee of Sparing Organizations of Tradeway) method.